Managed aquifer recharge of monsoon runoff using village ponds: performance assessment of a pilot trial in the Ramganga Basin, India - Alam, Mohammad Faiz; Pavelic, Paul; Sharma, Navneet; Sikka, Alok (MDPI, 2020)
The managed aquifer recharge (MAR) of excess monsoonal runoff to mitigate downstream flooding and enhance groundwater storage has received limited attention across the Indo-Gangetic Plain of the Indian subcontinent. Here, we assess the performance of a pilot MAR trial carried out in the Ramganga basin in India. The pilot consisted of a battery of 10 recharge wells, each 24 to 30 m deep, installed in a formerly unused village pond situated adjacent to an irrigation canal that provided river water during the monsoon season. Over three years of pilot testing, volumes ranging from 26,000 to 62,000 m3 were recharged each year over durations ranging from 62 to 85 days. These volumes are equivalent to 1.3–3.6% of the total recharge in the village, and would be sufficient to irrigate 8 to 18 hectares of rabi season crop. High inter-year variation in performance was observed, with yearly average recharge rates ranging from 430 to 775 m3 day-1 (164–295 mm day-1 ) and overall average recharge rates of 580 m3 day-1 (221 mm day-1 ). High intra-year variation was also observed, with recharge rates at the end of recharge period reducing by 72%, 88% and 96% in 2016, 2017 and 2018 respectively, relative to the initial recharge rates. The observed inter- and intra-year variability is due to the groundwater levels that strongly influence gravity recharge heads and lateral groundwater flows, as well as the source water quality, which leads to clogging. The increase in groundwater levels in response to MAR was found to be limited due to the high specific yield and transmissivity of the alluvial aquifer, and, in all but one year, was difficult to distinguish from the overall groundwater level rise due to a range of confounding factors. The results from this study provide the first systematic, multi-year assessment of the performance of pilot-scale MAR harnessing village ponds in the intensively groundwater irrigated, flood prone, alluvial aquifers of the Indo-Gangetic Plain.